2007
DOI: 10.1538/expanim.56.279
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ucp1, D2 (Dio2) and Glut4 (Slc2a4) mRNA Expression in Response to Short-Term Cold Exposure in the House Musk Shrew (Suncus murinus)

Abstract: The house musk shrew (Suncus murinus), or so-called suncus, is a coldintolerant mammal, but it is unclear why it is susceptible to low temperatures. Coldintolerance may be the result of lower thermogenic activity in brown adipose tissue (BAT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…BAT activation occurs at room temperatures between 4 - 16°C [9,13,21-23]. In our study, temperature exhibited trivial differences between IH (22.9 ± 2.5°C) and SIH cages (23.2 ± 2.1°C).…”
Section: Discussionmentioning
confidence: 51%
“…BAT activation occurs at room temperatures between 4 - 16°C [9,13,21-23]. In our study, temperature exhibited trivial differences between IH (22.9 ± 2.5°C) and SIH cages (23.2 ± 2.1°C).…”
Section: Discussionmentioning
confidence: 51%
“…In our present study, we further confirmed that five hours of HHP (0.66 ATA or 18.3% O2) daily for 5 consecutive days per week for 2 weeks before the start of heat exposure caused both weight loss and reduced BAT wet weight in rats. BAT activation occurs at temperatures between 4 and16 °C [51]. In our present study, all HHP experiments were conducted at 26 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we set out to develop a novel cancer therapeutic approach, termed adipose manipulation transplantation (AMT) that utilizes two unique abilities of white adipose tissue (WAT): 1) They can be readily extracted via liposuction and implanted via reconstructive surgery; 2) they can change into a BAT-like tissue, called browning or beiging (16,17), by upregulating essential transcriptional regulators or enzymes, such as the uncoupling protein 1 (UCP1), PPARG coactivator 1 alpha (PPARGC1A) or PR/SET domain 16 (PRDM16), involved in BAT development and function (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Similar to BAT, beige adipocytes have the capacity to convert energy to heat and contribute to whole-body energy expenditure (34).…”
Section: Introductionmentioning
confidence: 99%